ตำรับชาววัง: นวัตกรรมแห่งโภชณียประณีต: (Tam Rap Chao Wang: Innovation of the Food Refinement) - สวนสมุทร เปรม (วารสารวิชาการนวัตกรรมสื่อสารสังคม, 2017)
บทคัดย่อ ปัจจุบันร้านค้าจำนวนมากเขียนข้อความโฆษณาว่า “ตำรับชาววัง” หรือ “สูตรชาววัง” ในขณะที่รูปลักษณ์ของสินค้าและรสชาตินั้นไม่แตกต่างไปจากที่เห็นตามร้านค้าอื่นทั่วไปนัก จึงทำให้น่าสนใจว่าในความเป็นจริงแล้ว “อาหารชาววัง” นั้นแตกต่างจากอาหารทั่วไปตามท้องตลาดอย่างไร งานวิจัยชิ้นนี้จึงมุ่งศึกษาลักษณะสำคัญของอาหารชาววัง เพื่อแสดงให้เห็นความแตกต่างของอาหารในวัฒนธรรมราชสำนักกับอาหารที่บริโภคโดยทั่วไปในวัฒนธรรมชาวบ้าน ผลการวิจัยพบว่าความแตกต่างประการสำคัญของอาหารชาววังคือความคิดสร้างสรรค์ในการคิดค้นตำรับใหม่ๆ ความประณีตในการปรุง และความพิถีพิถันในการนำเสนอ นอกจากนั้นการเลือกสรรวัตถุดิบก็เป็นปัจจัยที่สำคัญที่ทำให้อาหารชาววังมีความพิเศษ การอ้างถึงตำรับชาววังจึงเป็นการสร้างมูลค่าเพิ่มให้แก่สินค้า ทั้งนี้หากมองการสร้างสรรค์อาหารของชาววังเป็นขนบอย่างหนึ่ง อาจกล่าวได้ว่าการ “เล่น” กับอาหารของคนไทยร่วมสมัยนั้นเป็นสมบัติที่สืบทอดมาจากประณีตศิลป์แห่งการประกอบอาหารของชนชั้นสูงในอดีต คำสำคัญ: อาหารไทย / ตำรับชาววัง / นวัตกรรมอาหาร / ความคิดสร้างสรรค์ / ประณีตศิลป์ Abstract Many shops are using ‘Tam Rap Chao Wang (recipe from the court) in their advertisement. The looks and the taste of their food are not much different from normal food in the other shops. It is interesting to examine what are the real recipes from the court and how are they special compared to food for common people. This research aims at studying the characteristics of recipes from the court, in order to define the difference between recipe from the court and from the common people. It is found that there are three elements: the inventing of the new and distinct recipes, the refinement in the cooking process and the elegant presentation. Additionally, the selection of ingredients is also important and make court cuisine exceptional. By mentioning the recipes from the court, the food shops are trying to add the dramatic value to their good. Nevertheless, if we are considering court cuisine as a convention, it is likely to say that ‘Len (playing)’ is a characteristics of Thai people. Contemporary Thai chefs who create an innovation of refinement in their dishes are in fact sustaining the heritage from the noble in the past. Keyword : Thai Food / Tam Rap Chao Wang / Innovation Food / Creativity / Refinement